(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The common sign of snake envenomation is hepatotoxicity or liver injury that is dependent on quality and quantity of venom. Objective:To clarify the effect of intraperitoneal (i.p.) injection of LD50 dose of Naja naja snake venom on the hepatic tissues of albino rats after 3 and 24 hr from envenoming respectively. Methods:The rats were divided into 3 groups, the first group served as a control group, while the other groups 2 and 3 were treated with the snake venom (0.05 µg/g body weight i.p) and sacrificed by decapitation after 3 and 24 hours of the snake venom injection respectively. The livers were isolated and histological sections were prepared. Results: Intraperitoneal LD50 for Naja naja snake cobra was determined in rats to be equal to 0.05 µg/g body weight. Histopathological changes in liver tissues after 3 hr from injection were congestion of the central veins, congested liver sinusoids, leucocytes infiltration, cytoplasmic vacuolization and nuclear pyknosis, cellular swelling and necrosis of some cells. While histopathological changes in liver tissues after 24h from injection were the same signs in addition to cellular swelling, necrosis and damage of the injured hepatocytes with acute inflammation cells infiltration. Conclusion:The injection of LD50 dose of Naja naja snake venomin rats can induce hepatic damage and hepatotixicity in albino rats. Keywords: Naja naja, snake venom, Rats, Liver, Histopathological changes.